Assessment of patients’ satisfaction in carotid surgery under local anaesthesia by psychometrical testing - a prospective cohort study - Attigah, Nicolas; Kutter, J.; Demirel, Serdar; Hakimi, Maani; Hinz, Ulf; Motsch, Johann; Böckler, Dittmar (European journal of vascular and endovascular surgery, 2011)
Methods - Between July 2008 and December 2008 102 consecutive patients undergoing CEA under local anaesthesia (LA) were prospectively evaluated. All patients were psychometrically assessed by the Hospital Anxiety and Depression Scale (HADS), the EuroQol and the Heidelberg peri-anaesthetic questionnaire (HPQ). Furthermore technical issues of cervical plexus block were assessed. - Results - Multivariate analysis with an HPQ sum-score of 98 points as a cut-off level for reduced patients’ satisfaction demonstrated that HADS-D scores of >9 (OR: 7.228; p = 0.003), insufficient intra-operative pain control (OR: 3.264; p = 0.0322) and complications due to plexus anaesthesia (OR: 3.794; p = 0.0370) were associated with a low patients’ satisfaction in carotid surgery under LA. - Conclusion - The efficacy of the plexus blockade in terms of pain control and side effects affects patients’ satisfaction in carotid surgery under LA. When choosing LA for patients undergoing carotid endarterectomy altered states of anxiety and mood reduce satisfaction in carotid surgery under LA and might compromise patients’ suitability for LA.